2017
DOI: 10.1098/rspa.2017.0136
|View full text |Cite
|
Sign up to set email alerts
|

Gyro-elastic beams for the vibration reduction of long flexural systems

Abstract: The paper presents a model of a chiral multi-structure incorporating gyro-elastic beams. Floquet–Bloch waves in periodic chiral systems are investigated in detail, with the emphasis on localization and the formation of standing waves. It is found that gyricity leads to low-frequency standing modes and generation of stop-bands. A design of an earthquake protection system is offered here, as an interesting application of vibration isolation. Theoretical results are accompanied by numerical simulations in the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…In parallel, new possibilities to dissipate the seismic energy in the superstructures themselves are emerging thanks to the contributions of auxetic materials [57] and metamaterials [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, new possibilities to dissipate the seismic energy in the superstructures themselves are emerging thanks to the contributions of auxetic materials [57] and metamaterials [52].…”
Section: Discussionmentioning
confidence: 99%
“…By another way but with the aim of reducing the effect of the waves on the structure, recent research on gyrobeams implemented in the structure itself [52] open a new perspective in chiral metamaterial design and in a wide range of applications in earthquake wave filtering. It has been demonstrated that the role of gyrobeams is primarily to create low-frequency 'energy sinks', in which waves generated by external excitations are channelled.…”
Section: New Dissipative Structuresmentioning
confidence: 99%
“…Due to the simplicity of expression (45) for the longitudinal field, the twelve boundary conditions (15), (16), and (17) reduce to four continuity conditions at the interfaces between the two substructures, which considering the quasi-periodicity condition (37), are equivalent to the following homogeneous linear system for the four amplitudes U…”
Section: Purely Axial Vibrations: System (0)mentioning
confidence: 99%
“…To improve the acoustic performances of the blocky system and to achieve ultra-low frequency stop bands, the blocks have been coupled with an elastic half-space model as a Winkler support. In this case, the low frequency branch has a non-vanishing frequency at the long wave-length limit and the opening of a ultra-low frequency band gap may be obtained (see Gei et al, 2009, Brun et al, 2012, Piccolroaz and Movchan, 2014, and Carta et al, 2017. Moreover, a convenient fine approximation of the dispersion functions of the Lagrangian model is pursued through the formulation of an equivalent continuum model.…”
Section: Introductionmentioning
confidence: 99%